Transaction Costs and Institutional Change of Trade Litigations in Bulgaria - Ножаров, Щерьо; Коралова–Ножарова, Петя (Научни трудове, 2018)
The methods of new institutional economics for identifying transaction costs of trade litigations in Bulgaria are used in the current paper. The main purpose of the model is to be forecasted the rational behaviour of trade litigation parties in accordance with the transaction costs in the process of enforced execution of the signed commercial contract. The implementation of the model is related to the more accurate measurement of transaction costs on microeconomic level.
Keywords: Транзакционни разходи; Нова институционална икономика; Реформа на съдебната система; Търговски спорове; Сива икономика